KONSEP AGAMA SUKU WANA TENTANG KEMATIAN, IMPLIKASINYA BAGI MISI KRISTEN DI WANA - Ronaldy Dada; Ermin Alperiana Mosooli (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
Wana, one of the tribes in Central Sulawesi, has a custom of demolishing houses and moving when one of the inhabitants dies. This custom is an expression of their fear of death. In theory, cultural activities around death are always associated with religious concepts. This study aims to explore the religious ideas behind their habits. The research method used was an ethnographic study using interviews as data collection techniques. Informants are 8 (eight) original Wana people. Data is analyzed through reduction, display, and conclusions/verification. The results show that the custom is related to the religious concept they professed regarding death. According to the Wana, death is associated with Pue, the end of everything, and caused by evil spirits. The Purpose of dismantling the house and moving after death is to avoid the influence of evil spirits against the living. For Christian mission activities that want to contribute to the development of Wana, the results show that religious concept needs to be transformed through a contextual approach. THE WANA RELIGIOUS CONCEPT OF DEATH, ITS IMPLICATIONS FOR THE CHRISTIAN MISSION IN THE WANA